Brain dominance and its relationship to the professional trends in high school students - Al- Sulami, Raed Mohammed; Al- Ghamdi, Salah Yahia (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the relationship between brain domain and professional tendencies in high school students in Taif governorate, if there are differences between individuals in professional tendencies based on brain domain and is there a difference in the order of professional tendencies of students with left- handed sovereignty of the brain and students with right- handed sovereignty for the brain and if there are differences in the professional tendencies of the study sample due to the specialization and differences in the dominant side of the brain in the sample of the study depending on the variable of specialization. To achieve the objectives of the study, the descriptive curriculum was followed and the sample consisted of 97 high school students. The researcher used the brain range (Torrance, 1988: rationing Murad, 1994) and the Professional tendencies Scale (Preparation of Ayad, 2011). The results of the study showed no correlation between brain domain and professional tendencies in high school students, as well as no statistically significant differences in the professional tendencies based on brain domain. There are also no statistically significant differences in the professional tendencies due to the variable specialization, and the left pattern is prevalent among students of scientific disciplines, while the integrated pattern is the dominant pattern among students of literary disciplines, and the descending order of the students with left- handed sovereignty differs from the brain and students with right- handed sovereignty of the brain. And In light of the results, the researcher recommends giving students a variety of tasks that help them use both sides of the brain more. And support the curriculum with activities that address the two hemispheres of the brain. And the use of the integrative learning model or the integrated educational model in the educational environment to achieve integration between the two hemispheres of the brain. And training teachers to employ different strategies to develop both sides of the brain, in proportion to the different learning and thinking styles of students.
Keywords: The brain dominance; the professional trends; High School Student